(Not) talking about justice: justice self-recognition and the integration of energy and environmental-social justice into renewable energy siting. Issue 3 (4th March 2018) - Bailey, Ian; Darkal, Hoayda
ABSTRACT: Renewable energy often provokes heated debate on climate change, energy security and the local impacts of developments. However, how far such discussions involve thorough and inclusive debate on the energy and environmental-social justice issues associated with renewable energy siting remains ambiguous, particularly where government agendas prioritise renewable energy and planning systems offer limited opportunities for public debate on value-based arguments for and against renewable energy developments. Using the concept of justice self-recognition, we argue for greater attention to public discussion of the justice dimensions of renewable energy to assist in developing mechanisms to integrate distributive and procedural fairness principles into renewable energy decision-making. To explore how justice is currently invoked in such contexts, we examine recent U.K. policies for renewable energy and public submissions to applications for small-scale wind energy projects in Cornwall, U.K. The analysis of public comments revealed that justice concerns were rarely discussed explicitly. Comments instead did not raise concerns as justice issues or focused implicitly on distributive justice, stressing local aesthetic, community and economic impacts, clean energy and climate change. However, the findings indicated limited discussion of procedural or participatory justice, an absence that hampers the establishment of coherent procedures for deciding acceptable impacts, information standards, public participation and arbitrating disputes. We conclude by suggesting procedural reforms to policy and planning to enable greater public expression of justice concerns and debate on how to negotiate tensions between energy and environmental-social justice in renewable energy siting decisions.